Computational analysis for industrial brush with discrete element method. - Tuan, Vu Anh
In this study, the discrete element computational method (DEM) is applied to analyze the dynamic problems of an industrial cup brush in cleaning process. At first, the method was created in order to analyze the flows of granular materials, and then it has been developed to be able to model more complex objects like rods or beams of brittle, elastic or composite materials. The recently designed flexible rod model in this research is composed of spherical particles linked together to form an elastic rod-type object. Theoretical model and the simulation model will be expressed to draw out the result as the total slipped length of the brush, the total contact area, and acting forces between rod tips and surfaces in comparison with different rotary speeds. The analyzed results show that the slipped distance of a brush on surfaces and forces between brush tips and surfaces increase when the rotary speed is increased, while the total contact area are smallest at a certain rotary speed of 450 rpm, and this total area is larger when either increasing or decreasing the rotary speed. Hence the most effective cleaning speed in the current research is 900 rpm. It is possible to simulate and evaluate several different types of brushes to find the best model and compatible parameters for surface cleaning and polishing process by applying the DEM flexible rod model.
Keywords: Discrete element method; Cleaning process; Industrial Brush